Effects of upper extremity fatigue on shooting accuracy, kinematics, and muscle activation in basketball players - Yasar, M. N.; Cilli, M.; Bakici, D.; Ay Gul, A. N.; Kalk, B.; Cinarli, F. S. (Kinesiologia Slovenica, 2025)
Fatigue is a critical determinant of sports performance, often impairing athletic precision and efficiency. This study investigated the effects of upper extremity fatigue on shooting accuracy, kinematics, and muscle activity in adolescent basketball players. Twelve participants (age: 15 ± 1.1 yrs; sports experience: 6 ± 2.7 yrs) performed free throws under pre- and post-fatigue conditions. Fatigue was induced through a structured protocol utilizing a graphical user interface to monitor exertion levels. Shooting accuracy was qualitatively assessed based on predefined shot outcome categories. Kinematic variables, joint angles, joint angular velocities, and ball trajectory parameters were analyzed alongside muscle activation of key upper extremity muscles. Post-fatigue analysis revealed a significant decrease in elbow angular velocity (-5.08%, p = 0.041, effect size = 0.59), indicating impaired joint coordination. Additionally, palmaris longus muscle activation declined (-4.68%, p = 0.028, effect size = 0.63), suggesting reduced wrist stability and grip control. Furthermore, shooting accuracy deteriorated, with a significant increase in the frequency of \'Airball\' (p < 0.05) and \'Short or uncontrolled shot did not score\' (p < 0.05) outcomes. However, no significant differences were observed in the \'Balanced and controlled shot, but did not score\' and \'Successful shot\' categories. These findings highlight the negative impact of fatigue on neuromuscular control and biomechanics, underscoring the importance of fatigue management strategies in basketball training to maintain shooting efficiency.